Survival of Xanthomonas campestris pv. campestris associated with soil and cauliflower crop debris under Brazilian conditions - Júnior, T. A. F. Silva [UNESP]; Silva, J. C. [UNESP]; Gonçalves, R. M. [UNESP]; Soman, J. M. [UNESP]; Passos, J. R.S. [UNESP]; Maringoni, A. C. [UNESP] (Springer Nature, 2020)
This study investigated the survival of Xanthomonas campestris pv. campestris (Xcc) in the soil, under field and controlled conditions, and associated with cauliflower crop debris. Under field conditions, the soil temperature influenced the survival of Xcc, and the bacterium survived from 4 to 7 days. Under controlled conditions, the soil type and temperature influenced Xcc survival. Depending on the texture, pH and organic matter content of the soil, the bacterium survived from 10 to 24 days. Xcc survived in the soil for 14 days at 20 °C, and for 4 days when incubated at 30 °C. The soil moisture did not influence Xcc survival of 14 days at the three moisture contents evaluated. Similar behaviour was observed regarding the survival of four Xcc strains in the soil. The longest period of Xcc survival associated with cauliflower debris was 255 days. Our results suggest that the soil is not an important source of inoculum for Xcc. Considering the survival periods of Xcc in cauliflower crop residues under the Brazilian conditions studied, we recommend crop rotation with non-host species of Xcc for 1 year. This information may also be useful for the management of black rot in other brassica-producing countries.
Keywords: Black rot; Brassica crop; Ecology, plant pathogenic bacteria